The Pacific Crest Trail : hiking America's wilderness trail - Smith, Bart, 1959- (Rizzoli, 2022)
This pocket-sized gift and souvenir photo book captures the beauty of America's quintessential wilderness hiking trail. From desert California to the Washington-Canada border, the compelling photography of Bart Smith brings the entire 2,650-mile trail to life.